Sex-typing of subject fields of study and employment among graduates in Costa Rica - Blanco, Laura Cristina (2018)
This paper used data from surveys of recent graduates from Costa Rican universities during the period 2000-2010 to test whether sex-typing of subject fields and areas of study were associated with the probability of being employed.  The findings indicated that graduates who studied male-dominated subject fields were more likely to be employed.  However, while women who entered predominantly male fields of study had an employment advantage, men who transgressed into female fields of study seem to be punished for it.  Schooling, job experience and class differences were also significant in explaining female employment, but less so for men.  Finally, an Oaxaca-Blinder decomposition for nonlinear models showed that only about a quarter of the gender employment gap was explained by differences in individual characteristics, suggesting the existence of discrimination in favor men.